A processing method with high efficiency for low density polyethylene nanofibers reinforced by aligned carbon nanotubes via nanolayer coextrusion. (24th February 2017) - Cheng, Junfeng; Pu, Hongting; Du, Jiang
Abstract: A method for large-scale processing of low density polyethylene (LDPE) nanofibers reinforced by aligned multi-walled carbon nanotubes (MWCNTs) is achieved via nanolayer coextrusion. The morphology and nano-sized diameter of the nanofibers are observed on scanning electron microscope. The prioritized alignment and dispersion of MWCNTs along the fiber axis are determined by transmission electron microscopy, polarized Raman spectra, and high resolution optical microscopy. The dispersion of MWCNTs in nanofibers is better than that in homologous micron-fibers. In addition, MWCNTs can promote the crystallization of LDPE in varying degrees which depend on the fiber diameter and MWCNTs content. As a result of the alignment of MWCNTs, the nanofibers exhibit enhanced mechanical properties. The tensile strength of LDPE(1 wt% MWCNTs) nanofibers is more than twice of pure nanofibers (without MWCNTs). The volume resistivity of the LDPE(MWCNTs) nanofiber mats containing 9 wt% MWCNTs can be reduced to 100 Ω cm. Graphical abstract: Highlights: A method for LDPE nanofibers reinforced by MWCNTs via nanolayer coextrusion. The dispersion of MWCNTs in nanofibers is better than that in micron-fibers. MWCNTs in LDPE fibers can promote the crystallization of LDPE. Nanofibers with aligned MWCNTs exhibit enhanced mechanical properties. The volume resistivity of LDPE(MWCNTs) nanofiber mats can be reduced to 100 Ω cm.